Spatially heterogeneous learning by a deep student machine - Hajime Yoshino (Physical Review Research, 2023)
Despite spectacular successes, deep neural networks (DNNs) with a huge number of adjustable parameters remain largely black boxes. To shed light on the hidden layers of DNNs, we study supervised learning by a DNN of width N and depth L consisting of NL perceptrons with c inputs by a statistical mechanics approach called the teacher-student setting. We consider an ensemble of student machines that exactly reproduce M sets of N-dimensional input/output relations provided by a teacher machine. We show that the statistical mechanics problem becomes exactly solvable in a high-dimensional limit which we call a “dense limit”: N≫c≫1 and M≫1 with fixed α=M/c using the replica method developed by Yoshino [SciPost Phys. Core 2, 005 (2020)10.21468/SciPostPhysCore.2.2.005] In conjunction with the theoretical study, we also study the model numerically performing simple greedy Monte Carlo simulations. Simulations reveal that learning by the DNN is quite heterogeneous in the network space: configurations of the teacher and the student machines are more correlated within the layers closer to the input/output boundaries, while the central region remains much less correlated due to the overparametrization in qualitative agreement with the theoretical prediction. We evaluate the generalization error of the DNN with various depths L both theoretically and numerically. Remarkably, both the theory and the simulation suggest that the generalization ability of the student machines, which are only weakly correlated with the teacher in the center, does not vanish even in the deep limit L≫1, where the system becomes heavily overparametrized. We also consider the impact of the effective dimension D(≤N) of data by incorporating the hidden manifold model [Goldt, Mézard, Krzakala, and Zdevorová, Phys. Rev. X 10, 041044 (2020)2160-330810.1103/PhysRevX.10.041044] into our model. Replica theory implies that the loop corrections to the dense limit, which reflect correlations between different nodes in the network, become enhanced by either decreasing the width N or decreasing the effective dimension D of the data. Simulation suggests that both lead to significant improvements in generalization ability.